Editorial: natural history of hepatitis delta virus‐induced liver disease ‐ less severe today but still needs attention. Issue 4 (31st July 2021) - Gençdal, Genco; Zeybel, Müjdat; Yurdaydin, Cihan
LINKED CONTENT: This article is linked to Palom et al paper. To view this article, visit https://doi.org/10.1111/apt.16485